Chronic Myeloid Leukemia (CML) in A 14-Year-Old - Catherine Halim; Leonardo Trisnarizki; Sisca Sisca (CV. Publikasi Indonesia, 2026)
Chronic Myeloid Leukemia (CML) is a myeloproliferative disorder accounting for approximately 2-3% of leukemias in children and adolescents, with an annual incidence of 1 in 1,000,000 individuals (approximately 10% of all CML cases). The median age of onset in children is 11-12 years. CML is caused by a reciprocal translocation of genes on chromosomes 9 and 22, resulting in the formation of the Breakpoint Cluster Region (BCR) gene on chromosome 22 with the Abelson leukemia virus (ABL) gene. The BCR-ABL protein has constitutive tyrosine kinase activity, leading to the activation of intracellular signal transduction pathways such as STAT, RAS, JUN, MYC, and Phosphatidylinositol-3 kinase. This case report concerns a 14-year-old girl with CML, a rare hematologic malignancy in children. The patient presented with abdominal enlargement and hardening for 2 months, abdominal pain, fever, and vomiting. Physical examination revealed splenomegaly (Schuffner 4). Laboratory tests revealed anemia (hemoglobin 7.3 g/dL) and leukocytosis (291,890 WBCs/mm³). Peripheral blood smear showed myeloid blasts and all stages of granulocyte maturation with basophilia and eosinophilia. Bone marrow aspiration confirmed chronic myeloid leukemia in the chronic phase with an M/E ratio of 25.5. BCR-ABL molecular testing revealed positive fusion of B2A2 and B3A2. This case highlights the aggressive presentation of pediatric CML characterized by massive splenomegaly and extreme leukocytosis, which differs from adult CML. Early recognition and timely diagnosis are essential to prevent disease progression and life-threatening complications such as leukostasis, bleeding, and splenic rupture.